Pembelajaran Sejarah dan Teacherpreneur - Abrar Abrar (Jurnal Pendidikan Sejarah, 2015)
The purpose ofthis paper reveals that the history teacher must be a teacherpreneur. The task of teacher preneur in implementing the learning history is to develop the ability to think creatively learners.It was motivated by the challenges of the times were more severe in all aspects of community life in the 21st century. The method used is literature study. Creative thinking skills can be cultivatedinthe teaching of historyby familiarizing students learn to solve problems. Through studying the history of learners solving problems is required to make a report based its findings workings historians. Teacherpreneur role is how to develop learning strategies that creative thinking was growing. Teacherpreneur is a teacher whois always doing good innovation to improve the knowledge and the learning process.